Feature subset selection method for dynamic software quality assessment - Kamaruddin, Siti Sakira; Deraman, Aziz; Yahaya, Jamaiah; Ahmad, Ruzita (2011)
This article presents a feature subset selection method for the purpose of selecting the appropriate attributes for software quality assessment. The existing software quality assessment models do not support dynamic assessment.In dynamic software quality assessment, new quality attributes can be added to the model as they emerge.Therefore, this work focuses on the development of an intelligent method that is able to learn and adapt new quality attributes into the model to establish dynamic software quality assessment.